T-STRONGLY OPERATOR - Tawfeeq, Bushra Jaralla (MAGISTRA, 2013)
In this paper ,We define and study the new types of operator we called â T-strongly operator ,T- strongly ï¡-operator, T-strongly semi operator and T-strongly semi âoperatorâ .Also some important theorems will be given and some properties will be studied.The concepts of T -open, T-semi -open will be used to define and study new types of open we calledâ T- strongly open ,T-strongly -open, T-strongly semi open and T- strongly semi –openâ and we study the relation among them ,also we define T-semi -regular and define and study new types of T- regular we called â T-strongly regular ,T- strongly - regular , T-strongly semi regular and T-strongly semi â regular â, we study the relation among them , as well as we define and study the new types of T- monotone operator we called â T- strongly monotone operator, T- strongly monotone â-operator, T- strongly monotone semi -operator, T- strongly monotone semiâ-operatorâ and we give some properties between them